Analysing Bibliometrics Trends: The Flipped Classroom Approach in Foreign Language Learning - Nuraeni Nuraeni; Nurul Fachrunnisa (JELITA, 2024)
This study aimed to investigate the adoption of the FC model for EFL learning. It considers research articles in the various journals and databases with ORCHID and Crossref indices between 2019 and 2023. Data analysis, for research trend mapping comparatively, used Vosviewer. This included especially recognizing the keywords that are in use nowadays, the articles and journals that are most cited, and the countries and institutions that are most influential. The result presented some interesting issues as follows.1) the countries with the highest link of collaborations were Malaysia, Iran, China, and Indonesia, while the most cited countries were Indonesia, Iran, China, Turkey and Malaysia. 2) The most used keywords in research on FC in EFL learning formed into four clusters. The most strength links were ‘flipped classroom’, ‘flipped learning’, ‘pedagogy’, ‘foreign language learning’, ‘COVID’ and ‘autonomous learning’. 3) The most used words in titles and abstracts form into 3 clusters with 'effect', 'perception', 'challenge', and 'COVID' being the most strength links 4) The most referenced authors include Zainuddin with 76 citations from 6 articles, Abdullah with 62 citations from 2 articles and Öztürk with 50 citations from 2 articles. 6) the most cited journals were the International Journal of Emerging Technologies in Learning (IJET).